188k views
3 votes
Which of the following equations is equivalent to 4[x + 2(3x – 7)] = 22x – 65?

28x – 7 = 22x – 65

28x – 56 = 22x – 65

10x – 14 = 22x – 65

16x – 28 = 22x – 65

2 Answers

6 votes

Answer: b) 28x - 56 = 22x - 65

Explanation:

4[x + 2(3x - 7)] = 22x - 65

start with the "inside" parenthesis: (distribute 2 into 3x - 7)

4[x + 6x - 14] = 22x - 65

add the like terms that are inside the parenthesis:

4[7x - 14] = 22x - 65

distribute 4 into 7x - 14:

28x - 56 = 22x - 65

User Karunesh Palekar
by
5.4k points
1 vote

Answer:


28x-56=22x-65

Explanation:

The given equation is

4[x + 2(3x – 7)] = 22x – 65

We expand the inner parenthesis to get;


4[x+6x-14]=22x-65

Simplify the expression on the right hand side.


4(7x-14)=22x-65

Expand using the distributive property to get;


28x-56=22x-65

User Majster
by
4.8k points